10 steps to creating an infographic a practical guide for non- designers - Wilkerson, Stephanie B.
"This book provides step-by-step guidance for developing high-quality infographics. Practical in its approach, 10 Steps to Creating an Infographic: A Practical Guide for Non-designers outlines a user-friendly process for developing infographics with a clearly defined purpose and powerful message. The book’s “how-to” approach makes infographic creation accessible for anyone who doesn’t have a background in graphic design or a budget for a graphic designer."